KONTRIBUSI MINAT BELAJAR SISWA TERHADAP HASIL BELAJAR MATA PELAJARAN GAMBAR TEKNIK DI JURUSAN TEKNIK BANGUNAN SMK NEGERI 1 PADANG - Alfioni .; M. Giatman, MSIE (Universitas Negeri Padang, 2019)
Abstract—. This research is backgrounded by the low learning outcomes of Technical Drawing of class XI in the Department of Building Engineering at SMK N 1 Padang. This study aims to reveal contribution of interest in learning towards the results of learning Technical Drawings of class XI in the Department of Building Engineering at SMK N 1 Padang. This type is descriptive correlational with a population of all students of class XI in the Department of Building Engineering at SMK N 1 Padang 2018/2019 academic year which amounted to 119 peoples. The sample was taken using a simple random sampling method with Slovin formula. The samples is 90 peoples. The type of data used is in the form of primary data and secondary data. Primary data is obtained through the dissemination of student learning interest questionnaires, while secondary data is report values in odd quantities of technical drawing subjects of class XI Building Engineering Department at SMK N 1 Padang 2017/2018 academic year. The results showed that interest in learning contributes to student learning outcomes by 27.35%. therefore we need to efforts increase strudents’ learning to be done to achieve good learning outcome.Keywords: Interest in Learning, Learning Outcomes, Tecnical Drawings